Optimization of a sustainable composition of fine-grained concrete for 3D-printing with partial substitution of sand with fly ash and slag waste - Murat A. Rakhimov; Zulfiya A. Aubakirova; Aliya K. Aldungarova; Ignacio Menéndez Pidal de Navascués; Zhangazy N. Moldamuratov (Нанотехнологии в строительстве, 2025)
Introduction. In the context of sustainable construction, one of the key challenges is the development of effective strategies for the management and recycling of fly ash and slag waste produced by thermal power plants. Recent studies confirm the potential of such waste as a partial substitute for conventional sand in concrete mixtures. However, most research focuses on conventional concrete and does not consider the specific requirements for rheological properties and interlayer adhesion, which are critical for 3D printing technology. Methods and Materials. The study used Portland cement CEM I 42.5N, fly ash and slag waste from the Ust-Kamenogorsk TPP, crushed sand, and the MasterGlenium superplasticizer. The concrete mix design was developed in stages: a base mix, a control mix (with an increased water-to-cement ratio), and experimental mixes with 25% and 50% sand replace ment by fly ash and slag waste. Samples were printed using a construction 3D printer (model S-6045) and tested for compressive strength, density, interlayer adhesion, and subjected to micro and nanostructural analysis. Results and Discussion. Experimental mixtures with 25% and 50% sand replacement showed reduced density and strength compared to the control mix. However, the 25% replacement mix maintained satisfactory strength, shape stability, and interlayer bonding. Micro and nanostructural analysis confirmed the relationship between structural compaction and physical-mechanical properties. Despite some limitations, the study demonstrated the potential of TPP-derived ash and slag waste as a viable component in 3D printing, provided the composition and extrusion parameters are optimized. Conclusion. The results indicate that replacing 25% of sand with fly ash and slag waste is optimal for fine-grained concrete mixtures intended for 3D printing. This approach improves resource efficiency and environmental sustainability without compromising the performance of the final products.